2017
DOI: 10.3389/fmicb.2017.02587
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Genotypic Eligible Methods for Salmonella Typhimurium Source Tracking

Abstract: Salmonellosis is one of the most common causes of foodborne infection and a leading cause of human gastroenteritis. Throughout the last decade, Salmonella enterica serotype Typhimurium (ST) has shown an increase report with the simultaneous emergence of multidrug-resistant isolates, as phage type DT104. Therefore, to successfully control this microorganism, it is important to attribute salmonellosis to the exact source. Studies of Salmonella source attribution have been performed to determine the main food/foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 208 publications
(395 reference statements)
0
49
0
3
Order By: Relevance
“…It is not surprising that the isolation of this serovar in outbreaks is strongly linked to the pork matrix. Additionally, as reported by Ferrari et al (77), currently several studies have demonstrated correlations between swine and human S. Typhimurium isolates.…”
Section: Discussionmentioning
confidence: 57%
“…It is not surprising that the isolation of this serovar in outbreaks is strongly linked to the pork matrix. Additionally, as reported by Ferrari et al (77), currently several studies have demonstrated correlations between swine and human S. Typhimurium isolates.…”
Section: Discussionmentioning
confidence: 57%
“…Such molecular typing approaches include pulsed-field gel electrophoresis (PFGE) (101, 102); multilocus sequence typing (MLST), which is based on variation in the sequences of seven housekeeping gene fragments (103,104); ribotyping (105); clustered regularly interspaced short palindromic repeat (CRISPR) typing (106,107); as well as other molecular methods. Since several comprehensive reviews about molecular Salmonella typing approaches have been published in the last few years (108)(109)(110)(111), and because more-modern next-generation sequencing methods are now emerging (see below), which are expected to replace these techniques in the near future, I do not further discuss these techniques here.…”
Section: Salmonella Serotypingmentioning
confidence: 99%
“…PFGE was used to analyze the important isolated strains (diarrheogenic E. coli, Salmonella and Yersinia enterocolitica) from L. ridibundus. The procedures were performed according to the protocols of each bacteria published by PulseNet (Curran et al, 2017;Ferrari, Panzenhagen, & Conte-Junior, 2017;Liang et al, 2014). The plugs digested with different enzymes, and electrophoresed with a recommendatory pulse times and hours at 20 V. For data analysis, *.tiff images of the gels were imported into the database of PFGE patterns.…”
Section: Pulsed-field Gel Electrophoresismentioning
confidence: 99%